ISLAMIC LAW ANALYSIS ON THE PRACTICE OF ONLINE RETAIL GOLD TRANSACTION - Aminudin Ma'ruf; Azhar Alam; Angrinda Anggih Umi Kulsum; Aditya Nurrahman (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2023)
This research is comprehensively investigating the mechanism of gold trading at the Tokopedia Gold site from an Islamic law perspective. This research further explains the Islamic views on the gold trade in retail through an online site. Two methods were used in completing this research; a qualitative descriptive method on the observation of the trading and library research. Upon supporting the research, three interviews with related customers are approached. Reviewing the terms and conditions of purchasing a product from Tokopedia Gold and literature review methods have also been taken into consideration. The paper found that the practice of purchasing gold through Tokopedia Gold is a full-payment purchase and avoiding the instalment method which might be against Islamic law. The research found that there is an existence of gharar when the purchaser does not possess the gold physically and does not know the existence of the gold. This paper recommends that the specifications of gold must be specified by a seller and spreading the knowledge of gold trading from an Islamic perspective.